2017
DOI: 10.1371/journal.pone.0183957
|View full text |Cite
|
Sign up to set email alerts
|

Trans-synaptic degeneration in the optic pathway. A study in clinically isolated syndrome and early relapsing-remitting multiple sclerosis with or without optic neuritis

Abstract: ObjectiveIncreasing evidence suggest that neuronal damage is an early and diffuse feature of Multiple Sclerosis (MS) pathology. Analysis of the optic pathway may help to clarify the mechanisms involved in grey matter damage in MS. Purpose of our study was to investigate the relationship between inflammation and neurodegeneration and to achieve evidence of trans-synaptic degeneration in the optic pathway in MS at clinical onset.Methods50 clinically isolated syndromes/early relapse-onset MS (CIS/eRRMS) with mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 39 publications
(34 reference statements)
1
32
0
1
Order By: Relevance
“…18 In conclusion, the diffusion alterations identified within the OR of HON patients' lesions within the postchiasmatic visual pathway further strengthen the concept of anterograde transsynaptic degeneration in inflammatory autoimmunity involving the visual pathway. 45 In addition to previous results documenting trans-synaptic degeneration within 1 year after an ON, 8,11 we have shown that a single clinical ON episode can also induce long-term (mean [SD] duration after ON was 8.3 [3.7]) WM alterations, which have also been related to neuronal damage in longstanding disease course. 39 Retinal damage has also been shown in large cohorts comparing NON eyes with healthy controls but was less severe compared with HON eyes.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…18 In conclusion, the diffusion alterations identified within the OR of HON patients' lesions within the postchiasmatic visual pathway further strengthen the concept of anterograde transsynaptic degeneration in inflammatory autoimmunity involving the visual pathway. 45 In addition to previous results documenting trans-synaptic degeneration within 1 year after an ON, 8,11 we have shown that a single clinical ON episode can also induce long-term (mean [SD] duration after ON was 8.3 [3.7]) WM alterations, which have also been related to neuronal damage in longstanding disease course. 39 Retinal damage has also been shown in large cohorts comparing NON eyes with healthy controls but was less severe compared with HON eyes.…”
Section: Discussionsupporting
confidence: 67%
“…5 Combining structural and quantitative MRI with optical coherence tomography (OCT), which allows rapid in vivo quantification of both neuronal (ganglion cell layer [GCL]) and axonal (retinal nerve fiber layer [RNFL]) retinal tissues, nearly the entire visual pathway can be probed both in the presence and in the absence of an acute inflammatory event that manifests clinically as optic neuritis (ON). As a consequence, the visual pathway could represent an ideal model to assess trans-synaptic degeneration in MS [6][7][8] as a model system for different functional CNS loops.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Others have proposed that it could be caused by primary degeneration of the GCIPL neurons due to MS. Lastly, many have suggested that lesions in the optic radiation via trans-synaptic degeneration could lead to loss of retinal ganglion cells and their axons. Indeed, Puthenparampil et al [5] found an inverse correlation between the thickness of the temporal RNFL and the ipsilateral optic radiation white matter lesion load (r = −0.7, p < 0.05) in patients with MSON. Furthermore, they observed an inverse correlation between the nasal RNFL and the contralateral optic radiation white matter lesion load (r = −0.8, p < 0.01 for both the superior and inferior nasal quadrant).…”
Section: Pathophysiological Insightsmentioning
confidence: 98%
“…They speculated that this might have arisen from retrograde degeneration owing to optic neuritis, but the concurrent presence of specific atrophy in numerous other WM structures throughout the brain seemed to suggest that OC atrophy may have been part of a generalized atrophic process. On the other hand, there is evidence that in patients with optic neuritis, the ON inflammation cooperates with optic radiation WM lesion load to determine a more diffuse damage specifically in the optic pathway, owing to trans‐synaptic degeneration that links inflammation and neurodegeneration in these patients (Puthenparampil et al, ). Another potential confounding issue that we did not consider in selecting our MS patients was the possibility that atrophy of the OC could have occurred owing to direct OC inflammation, similar to optic neuritis.…”
Section: Discussionmentioning
confidence: 99%